Cyberbullying among adolescents during the COVID-19 pandemic: an integrative review (Research, Society and Development, 2022)
This study aimed to identify how many and which studies were related to cyberbullying and adolescence during the COVID-19 pandemic period, as well as to analyze them according to their objectives and results. This is an integrative review, in which PubMed, ERIC and Scopus databases were used, with selection criteria for articles published in the period from 2020 to 2022. The following keywords were used: adolescent; cyberbullying; pandemic; covid. In all, 36 scientific articles were found, of which 28 did not meet the inclusion criteria, with a total of eight articles analyzed. As a data analysis technique, we separate the Objectives and Results of each article. As a result, we found research that carried out interventions to reduce cyberbullying, articles that related cyberbullying with other behaviors and realities of adolescence such as degrees of loneliness, moral disengagement, compulsive internet use, stress and abuse. Another relevant result achieved and discussed was the prevalence of cyberbullying, before and during social isolation, which did not have a significant increase, opening possibilities for further studies with the objective of identifying this effect.